Clinical and Instrumental Diagnostics in Patients With Acute Dizziness - E. V. Shevchenko; G. R. Ramazanov; S. S. Petrikov (Неотложная медицинская помощь)
INTRODUCTION Acute dizziness (AD) can be a manifestation of a large number of diseases, including both benign pathology and life-threatening conditions, particularly stroke. In his diagnostic search, the doctor can adhere to two tactics: the exclusion of peripheral vestibulopathies (the most common cause of AD), and the identification of symptoms of damage to the central nervous system.AIM OF STUDY Comparison of instrumental research methods data with the clinical picture in patients with AD.MATERIAl AND METHODS We examined 160 patients admitted to N.V. Sklifosovsky with the only or leading complaint of dizziness. In all patients neurological status was assessed, Dix–Hallpike (DH) and Pagnini–McClure  (PMC) positional maneuvers, Halmagyi–Curthoys (HC) test, duplex scan of brachiocephalic arteries, transthoracic echocardiography, computed  tomography, and magnetic resonance imaging were performed. brain. In  patients with suspected cardiogenic cause of dizziness, the diagnostic search included 24-hour Holter ECG monitoring.RESUlTS The frequency of some symptoms differed in patients with acute cerebrovascular accidents (ACVA) and other diseases. In patients with stroke such symptom, as postural instability was statistically more frequently detected than in patients with other causes of dizziness (44% vs. 6%, p<0.05). The sensitivity and specificity of this symptom in patients with stroke was 44% and 94%, respectively. Horizontal nystagmus, changing direction depending on the gaze setting, was detected in 5 patients with ACVA (31%) and was not observed in patients with other diseases. The sensitivity of the symptom was 31% and the specificity was 100%.Positional maneuvers of DH and PMC were positive only in patients with be-nign paroxysmal positional vertigo.CONClUSION The main symptoms that make it possible to suspect a stroke in patients with acute dizziness are postural instability and horizontal nystagmus, which changes direction. The sensi-tivity and specificity of severe postural instability were 44% and 94%, and 31% and 100% for nystagmus  reversing direction. Positive Dix–Hallpike and Pagnini–McClure positional maneuvers can rule out stroke and establish the diagnosis of benign  paroxysmal positional vertigo in patients with acute dizziness. The Halmagyi–Curthoys test can be positive both in peripheral vestibulopathies (vestibular  neuronitis, Meniere’s syndrome, labyrinthitis), and in stroke in the basin of the anterior inferior cerebellar artery and cannot be used to confirm peripheral vestibulopathy. Holter daily monitoring of electrocardiography reveals cardiac conduction abnormalities as a cause of dizziness in patients  with episodes of non-systemic dizziness.